Maharadia Lawana. [anthology].
The story narrates the adventures of the monkey-king, Maharadia Lawana, whom the Gods have gifted with immortality.
Found in: Philippine Folk Literature: The Epics. (GR 325 P48 2001 v.8)
Keywords: Literature-Collections.